A study on the cutting errors of the tooth profiles of the cycloidal gears manufactured in CNC milling machine - Ozel, Cihan; Ortac, Yunus (Inderscience Enterprises Ltd, 2016)
In this study, the cycloidal gears are machined by the end mill in CNC milling machine. These gears are manufactured by varying the design and the cutting parameters in generated CAM program. It is noticed that the magnitude of the cutting parameters shortens it while the magnitude of the design parameters extends the cutting time of the gears. Then, the tooth dimensions are both measured by a calliper and calculated by using mathematical relations. It has been observed that the measured values are in good agreement with the calculated values. Additionally, an analytical approach is presented to investigate the cutting errors of the tooth profiles. A MATLAB program is developed by using this approach. The design parameters of the gear are varied in the program, and the errors are interpreted graphically. As a result, it is noticed that these errors increase regarding to increment values of the design parameters.
Keywords: cycloidal gear; end mill; CNC milling; cutting errors